Assessment of Road Traffic Noise and Associated Health Complaints- Analysis Through Structural Equation Model - Dubey, Payal; Singh, Kunwar Raghvendra; Goyal, Sudhir Kumar (International Journal of Integrated Engineering, 2025)
Noise pollution due to the increasing number of vehicles is one of the foremost concerns in the modern era, which hampers the humans physical and mental well-being of people specially residing in developing countries. Various studies have reported associations between noise exposure and heart diseases, insomnia, stress, annoyance, and high blood pressure. These findings motivate us to assess the situation within our area. This paper aims to analyze the effects of traffic noise on dwellers living adjacent to the national highway (NH-44) stretch of 45 kilometers from Chatta to Township in Mathura. The Present study is based on the subjective analysis of the questionnaire on traffic-related noise pollution. The survey was conducted both online and offline mode. The data gathered from 740 respondents were analyzed through structural equation modeling (SEM). Absolute fit, incremental fit, and parsimonious fit indices were used to evaluate the hypothesis and validate the developed model.  The study revealed that the factor analysis has given the three components of with overall variance of 49.306. Furthermore, analysis with a fit indices like chi square (100.04), DF (1.640), RMR (0.043), RMSEA (0.029), NFI (0.946), RFI (0.931), IFI (0.978), TLI (0.972), CFI (0.978), PNFI (0.740), and PCFI (0.765), respectively. The established model identified associations among user characteristics, noise effect and diseases. This study aims to provide assistance to policymakers in addressing the aforementioned difficulties. Further research should be conducted to explore potential strategies or interventions for mitigating the impact of traffic noise. The implementation of noise barriers, enforcement of traffic regulations, and provision of informative instructional signage are measures aimed at raising public awareness regarding the effects of traffic noise.